Normative data for regional sweat sodium concentration and whole-body sweating rate in athletes. Issue 4 (16th February 2016) - Baker, Lindsay B.; Barnes, Kelly A.; Anderson, Melissa L.; Passe, Dennis H.; Stofan, John R.
Abstract: The purpose of this study was to establish normative data for regional sweat sodium concentration ([Na + ]) and whole-body sweating rate in athletes. Data from 506 athletes (367 adults, 139 youth; 404 male, 102 female) were compiled from observational athlete testing for a retrospective analysis. The participants were skill/team-sport (including American football, baseball, basketball, soccer and tennis) and endurance (including cycling, running and triathlon) athletes exercising in cool to hot environmental conditions (15–50°C) during training or competition in the laboratory or field. A standardised regional absorbent patch technique was used to determine sweat [Na + ] on the dorsal mid-forearm. Whole-body sweat [Na + ] was predicted using a published regression equation ( y  = 0.57 x +11.05). Whole-body sweating rate was calculated from pre- to post-exercise change in body mass, corrected for fluid/food intake (ad libitum) and urine output. Data are expressed as mean ± SD (range). Forearm sweat [Na + ] and predicted whole-body sweat [Na + ] were 43.6 ± 18.2 (12.6–104.8) mmol · L –1 and 35.9 ± 10.4 (18.2–70.8) mmol · L –1, respectively. Absolute and relative whole-body sweating rates were 1.21 ± 0.68 (0.26–5.73) L · h –1 and 15.3 ± 6.8 (3.3–69.7) ml · kg –1  · h –1, respectively. This retrospective analysis provides normative data for athletes' forearm and predicted whole-body sweat [Na + ] as well as absolute and relative whole-body sweating rate across a range of sports and environmental conditions.